Less hunger, better health and more wealth: the benefits of knowledge sharing in Malawi’s Orange-Fleshed Sweet Potato project - Ernawati, Abidin P.; Nyekanyeka, T.; Heck S; McLean S; Mnjengezulu G; Chipungu, Felistus P.; Chimsale, R.; Botha, B. (2013)
Agricultural researchers, NGOs and farmers in Malawi have pooled their knowledge and resources to develop and distribute new vitamin-enriched and drought-resistant sweet potato varieties, and to devise and promote new commercial activities that will help its spread.